Боги и Герои - Кун Николай Альбертович (Библиотека детской литературы)
Экземпляры: ф.7 (2004) / Инвентарный номер: 48351 / Цена: / Сис.шифр: 82.3(0) / Авт.знак: К 91 / ГРНТИ: 17.71.91 / ББК: 82.3(0)-6